Socio-Emotional Behaviors of Japanese Children during the COVID-19 Pandemic: A Cross-Sectional Study - Yusuke Moriguchi; Chifumi Sakata; Xianwei Meng; Naoya Todo (SAGE Open, 2024)
A novel coronavirus, SARS-CoV-2, has spread widely throughout the world. To reduce the spread of infection, children are prevented from going to school and have fewer opportunities for in-person communication. Such changes in the everyday lives of children might influence their socio-emotional behaviors; however, the whole picture of the possible impact was not well known. This study examined socio-emotional behaviors of Japanese children (aged 4–9) during the pandemic and compared the data to the data before the pandemic. Children’s socio-emotional behaviors in an everyday context was assessed using the parent-reported Strengths and Difficulties Questionnaire. The results indicated that during the pandemic, children were more prosocial and experienced more problems in their peer relationships, but no differences were found in emotional symptoms, conduct problems, hyperactivity between before and during the pandemic. The findings suggest that the COVID-19 pandemic has mixed impacts on children’s socio-emotional behaviors, implying that this topic should be considered in broader and fuller perspectives.